Horners Syndrome-Torticollis Relation; a Case Report [Horner Sendromu Tortikollis Iliskisi; bir Olgu Sunumu] - Ilknur Can (Medicine Science, 2016)
Horner Syndrome is a rare condition characterized with ptosis, miosis, unilateral anhidrosis and rarely enophtalmos resulting from the sympathetic innervation loss by interruption of oculosymathetic pathway. Congenital muscular torticollis is a musculoskeletal system malformation resulting from fibrosis, therefore shortening of sternocleidomastoid muscle. In this report, Horners syndrome secondary to congenital muscular torticollis and diagnosis in rehabilitation period are discussed. Three-month-old baby girl was referred to our unit by pediatrics clinic with congenital muscular torticollis diagnosis. Her history comprised of cesarean delivery following a 34-week pregnancy as twin, and no intensive care need; her parents realized asymmetry in neck when she was a-month-and-a-half old and they admitted to pediatrics. Craniofacial asymmetry, cervical left lateral flexion, restricted left rotation and olive sign were detected in physical examination. During rehabilitation, anhidrosis in the right side of face, soft left miosis and ptosis were also observed, and patient was diagnosed with Horners syndrome. Other possible reasons were ruled out with differential diagnosis and etiology was linked to torticollis. Consequently, while evaluating patients with torticollis, it must be considered that Horners syndrome, rarely accompanies, and since clinical findings may be soft, diagnosis may easily be missed out. [Med-Science 2016; 5(3.000): 829-37]